Efficacy of a Communication Toolkit to Optimize Palliative Care Communication in the Surgical Intensive Unit - Kathryn Cary; Aubrey Place; Marta McCrum; Joanna Grudziak; Lauren McGuire (Patient Experience Journal)
Data demonstrates patients benefit from the experience of specialty palliative care providers for advance care planning and prioritizing quality of life, regardless of diagnosis or stage of illness. Despite these benefits, many intensive care units (ICUs) show low utilization of palliative care. The purpose of this study was to evaluate the ability of a bedside communication toolkit to improve communication between family members and caregivers of surgical ICU patients and the ICU team, particularly in the context of medical updates and decision-making. A pilot bedside communication tool was completed by fifty family members of trauma and emergency general surgery (EGS) patients. Participants then completed a survey to provide feedback on the toolkit. The majority of family members felt the toolkit helped them to formulate questions for the team and agreed they were more informed as a result of the toolkit. The majority disagreed the toolkit was emotionally upsetting to read through. The perceived benefit by family members/decision makers of surgical ICU patients offers many opportunities for further investigation and integration of the toolkit into practice in the ICU and beyond. A communication toolkit may improve communication between patient providers and family members, particularly in key medical decision-making discussions.